Diffuse optical tomography of breast cancer during neoadjuvant chemotherapy: a case study with comparison to MRI - Choe, Regine; Corlu, Alper; Lee, Kijoon; Durduran, Turgut; Konecky, Soren D; Grosicka-Koptyra, Monika; Arridge, Simon R; Czerniecki, Brian J; Fraker, Douglas L; DeMichele, Angela; Chance, Britton; Rosen, Mark A; et al. (Medical physics (Lancaster), 2005)
We employ diffuse optical tomography (DOT) to track treatment progress in a female subject presenting with locally advanced invasive carcinoma of the breast during neoadjuvant chemotherapy. Three-dimensional images of total hemoglobin concentration and scattering identified the tumor. Our measurements reveal tumor shrinkage during the course of chemotherapy, in reasonable agreement with magnetic resonance images of the same subject. A decrease in total hemoglobin concentration contrast between tumor and normal tissue was also observed over time. The results demonstrate the potential of DOT for measuring physiological parameters of breast lesions during chemotherapy.